Cardiovascular function is better in veteran football players than age‐matched untrained elderly healthy men. Issue 1 (4th December 2013) - Schmidt, J. F.; Andersen, T. R.; Andersen, L. J.; Randers, M. B.; Hornstrup, T.; Hansen, P. R.; Bangsbo, J.; Krustrup, P.
<x xml:space="preserve">Abstract</x> The aim of the study was to determine whether lifelong football training may improve cardiovascular function, physical fitness, and body composition. Our subjects were 17 male veteran football players (VPG; 68.1 ± 2.1 years) and 26 healthy age‐matched untrained men who served as a control group (CG; 68.2 ± 3.2 years). Examinations included measurements of cardiac function, microvascular endothelial function [reactive hyperemic index (RHI)], maximum oxygen uptake (VO2max), and body composition. In VPG, left ventricular (LV) end‐diastolic volume was 20% larger (P < 0.01) and LV ejection fraction was higher (P < 0.001). Tissue Doppler imaging revealed an augmented LV longitudinal displacement, i.e., LV shortening of 21% (P < 0.001) and longitudinal 2D strain was 12% higher (P < 0.05), in VPG. In VPG, resting heart rate was lower (6 bpm, P < 0.05), and VO2max was higher (18%, P < 0.05). In addition, RHI was 21% higher (P < 0.05) in VPG. VPG also had lower body mass index (P < 0.05), body fat percentage, total body fat mass, android fat percentage, and gynoid fat percentage (all P < 0.01). Lifelong participation in football training is associated with better LV systolic function, physical fitness, microvascular function, and a healthier body composition. Overall, VPG have better cardiovascular function compared with CG, which may reduce their cardiovascular morbidity and mortality.